Ionic Liquid Ordering at an Oxide Surface1. Issue 21 (8th September 2016) - Wagstaffe, Michael; Jackman, Mark J.; Syres, Karen L.; Generalov, Alexander; Thomas, Andrew G.
Abstract: The interaction of the ionic liquid [C4 C1 Im][BF4 ] with anatase TiO2, a model photoanode material, has been studied using a combination of synchrotron radiation photoelectron spectroscopy and near‐edge X‐ray absorption fine structure spectroscopy. The system is of interest as a model for fundamental electrolyte–electrode and dye‐sensitized solar cells. The initial interaction involves degradation of the [BF4 ] − anion, resulting in incorporation of F into O vacancies in the anatase surface. At low coverages, [C4 C1 Im][BF4 ] is found to order at the anatase(101) surface via electrostatic attraction, with the imidazolium ring oriented 32±4° from the anatase TiO2 surface. As the coverage of ionic liquid increases, the influence of the oxide surface on the topmost layers is reduced and the ordering is lost. Abstract : The interaction of the ionic liquid [C4 C1 Im][BF4 ] with anatase TiO2, a model photoanode material, is studied using a combination of synchrotron radiation photoelectron spectroscopy and near‐edge X‐ray absorption fine structure spectroscopy.